Development of an online teaching platform to improve access to postgraduate pathology training in sub-Saharan Africa - Byers, Richard J; Byers, Anita J; Mumba, Chibamba; Mutuku, Angela; Singer-Rupp, Jennifer; Wilson, Michael; Fleming, Kenneth; Sayed, Shahin (Frontiers in Medicine, 2024)
Resource barriers to provision of accessible training in cancer diagnosis in Lower and Middle-Income Countries (LMICs) limit the potential of African health systems. Long term provision via teaching visits from senior pathologists and trainee foreign placements is unsustainable due to prohibitive costs of travel and subsistence. Emerging eLearning methods would allow pathologists to be trained by experts in a cheaper, more efficient and scalable way.Aim was to develop an online teaching platform, starting with haematopathology, for trainee pathologists in sub-Saharan Africa, initially Nairobi, Kenya and Lusaka, Zambia.Course materials were prepared for both Canvas and the Zoom eLearning platforms using digitally scanned slides of lymph nodes and bone marrow trephines. Initial in-person visits were made to each site to establish trainee rapport and maximise engagement, evaluate different methods and course content, and obtain feedback to develop project. The knowledge of trainees before and after course completion was used to measure initial effectiveness. Online teaching with the preferred platform is to be continued for 1 year before re-evaluation for longer term effectiveness.Canvas was selected as the preferred delivery platform as it is freely available and has good functionality to support all required tasks. Face to face teaching was considered optimal to establish the initial rapport necessary to maximise subsequent engagement with online teaching. Challenges have included sub-optimal internet speeds and connections, and scheduling issues. Weekly online haematopathology teaching sessions using live image capture microscope sessions, Zoom and Canvas have been delivered to students in Kenya and Zambia, with good attendance and interaction in case discussions.Our team has successfully designed and delivered an online training programme in haematopathology to trainees in Kenya and Zambia, ongoing now for over a year. This project is now being scaled to other sub-Saharan countries and to other subspecialities.